Respuesta :
Hey there! :)
Perpendicular to y = -3x + 5 ; passes through (2, 6).
Our slope is -3. We know this because it is in the "m" position from slope-intercept form. However, since our equation we're looking for is perpendicular to our given one, we must find the negative reciprocal of -3.
A negative reciprocal is simply a number that is flipped and either given a negative or gets a negative removed.
So the negative reciprocal of -3 is 1/3. This means that our new slope is 1/3.
Now, using point-slope form ( y-y₁=m(x-x₁) ), our new slope (1/3) & (2, 6) , let's find our new equation!
y-y₁=m(x-x₁) y - (6) = 1/3(x - 2)
Simplify.
y - 6 = 1/3x - 2/3
~Hope I helped!~